En garde! Redefinition of Nebela militaris (Arcellinida, Hyalospheniidae) and erection of Alabasta gen. nov - Duckert, Clément; Blandenier, Quentin; Kupferschmid, Fanny A L; Kosakyan, Anush; Mitchell, Edward A D; Lara, Enrique; Singer, David (European journal of protistology, 2018)
Molecular data have considerably contributed to building the taxonomy of protists. Recently, the systematics of Hyalospheniidae (Amoebozoa; Tubulinea; Arcellinida) has been widely revised, with implications extending to ecological, biogeographical and evolutionary investigations. Certain taxa, however, still have an uncertain phylogenetic position, including the common and conspicuous species Nebela militaris. A phylogenetic reconstruction of the Hyalospheniidae using partial sequences of the mitochondrial Cytochrome Oxidase Subunit 1 (COI) gene shows that N. militaris does not belong to genus Nebela, but should be placed in its own genus. The morphological singularities (strongly curved pseudostome and a marked notch in lateral view) and phylogenetic placement of our isolates motivated the creation of a new genus: Alabasta gen. nov. Based on their morphology, we include in this genus Nebela kivuense and Nebela longicollis. We discuss the position of genus Alabasta within Hyalospheniidae, and the species that could integrate this new genus based on their morphological characteristics.
Keywords: fylogeneze; druhová specificita; DNA, Protozoan; Species Specificity; Lobosea; Phylogeny; protozoální DNA; Electron Transport Complex IV; ribozomální DNA; respirační komplex IV; DNA, Ribosomal